SA’I DALAM PERSPEKTIF HADIS: (Menyingkap makna di Balik Ritual Haji dengan Metode Maudhu’iy) - Dr. Djaenab Djaenab (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2016)
Sa'i is one of worship that are part of the implementation of the Hajj rituals in a way to travel and jog in accordance with the provisions of Shari'ah. Implementation sa'i have a bottom in some traditions that became the foundation for determining the proposition or law sa'i. According to the authors sa'i is an obligation for every Muslim to perform the Hajj. Number sa'i Hadith has been described by the prophet, so jogged between safa and dignity seven times is a series that can not be separated in the pilgrimage. Similarly, the legal basis of the procedures of sa'i. Strong enough to see how Rasullah give an example to his friend in implementing sa'i